44 Nurse led heart failure management at a district general hospital demonstrates significantly improved outcomes in terms of optimisation to evidence based maximum dose of key heart failure medication. (June 2018) - Strawbridge, Martyn; Giblett, Dawn; Gosling, Oliver
Abstract : Background: The incidence and prevalence of HF (heart failure) secondary to LVSD (left ventricular systolic dysfunction) is increasing. National and international audits demonstrate that most patients are treated with an evidence based medication regime; however very few patients are adequately optimised to the evidence based dose. Angiotensin converting enzyme inhibitors have been used for the last 30 years and demonstrate a clear improvement in mortality and morbidity; with this improvement having a dose response. Beta blockers have also shown a survival advantage at higher doses. Our nurse led HF service was commissioned in 2013 with the remit to reduce the number of hospital admissions and readmissions due to HF as a primary diagnosis. This service also manages outpatients with LVSD with regards to medication optimisation, education and support. Once these objectives are met, patients are discharged from the service. Our team of nurses have received specialist training in physical examination and are registered independent prescribers. Aim: To collate and analyse local data for outpatients with a diagnosis of HF who are reviewed by the nurse led HF team. The purpose of this audit was to determine areas of good practice (against NICE and ESC guidance) and to identify areas for improvement if necessary. Method: Patient group ll patients with a diagnosis of LVSD seen through the outpatient department by the nurse led HF team and discharged from the HF nurse led service on maximum tolerated medications. Data collection: Retrospective data from Jan 2016 – Nov 2017 was collated and Microsoft Excel was used for analysis. Results: 373 patients had a diagnosis of LVSD. 71 % were male with an average age of 72, and 30 % of these patients were over 80 years of age. 75 % of patients with LVSD had an EF (ejection fraction) of <35%. 156 patients were discharged from the service during the 23 month period with a diagnosis of LVSD and an EF <35%. 75 % of these patients were discharged on maximum tolerated evidence based doses of key heart failure medication. Conclusion: We have demonstrated that a nurse led HF service results in a high percentage of patients receiving and tolerating the evidence based dose of key HF medication. This result is in contrast to other national and international audits where there is a persistent problem regarding full optimisation of these drugs. Other centres may wish to adopt a similar model of appropriately skilled specialist nurses to support and manage HF patients.